Diversidade de bactérias cultiváveis associadas às colônias sadias e necrosadas do zoantídeo Palythoa caribaeorum (Cnidaria, Anthozoa) dos recifes costeiros de Carapibus, Paraíba - Silva, Roberta Mayrielle Souza da (2015)
The microbial communities play a fundamental role in the health of coral and their changes can lead to the onset of disease. Many diseases affect coral reefs in several parts of the world, however, little is known about the pathogenic agents and the factors that trigger the pathological process. In coastal reefs of Carapibus Beach of Conde (Paraiba state, Brazil), a tissue necrosis affects the zoanthid Palythoa caribaeorum. This study aimed to compare the diversity of culturable bacteria in the samples of healthy and necrotic tissue from the P. caribaeorum colony collected from the Carapibus reefs. The present work aimed also to analyze the production of proteolytic enzymes by isolated bacteria. The density of total heterotrophic bacteria in the necrotic tissue was higher than in healthy tissue of P. caribaeorum. Phylogenetic analysis of isolated bacteria based on the partial 16S rRNA gene sequences revealed that the majority of bacterial strains belonged to the Bacilli class of Firmicutes phylum (65.2%), followed by the Gamma Proteobacteria class (34.7%) of Proteobacteria phylum. The genus Bacillus was dominant among the strains of healthy tissue of P. caribaeroum, while among the bacteria of necrotic tissue the Bacillus and Vibrio were the most abundant. The higher number of strains belonged to the Vibrio genus were found in necrotic tissue (42.1%) in comparison with healthy tissue (9.6%). Among bacteria from healthy tissue were found also Staphylococcus sp. isolate and from necrotic tissue Marinobacter spp. and Alteromonas spp. isolates. Among the isolates from healthy tissue only Bacillus spp. showed proteolytic activity, while proteolytic isolates from necrotic tissue belonged to the genera: Bacillus, Vibrio, Alteromonas and Marinobacter. The data suggest that bacteria of the genus Vibrio and proteolytic bacteria may play a role in the development of tissue necrosis of zoanthid studied.